The argumentative mind fact as a didactic strategy for teaching critical thinking in political science students - Araujo Ferrer , Felipe Rafael; Valenzuela , Luz (Frónesis, 2021)
Developing critical thinking has been one of the most relevant goals and commitments of the educational reform, carried out in Venezuela and in other countries since the last decade of the last century, this especially in those disciplines that by their nature require the spirit in its formation and exercise such as Political Science. This training will allow them to be useful and productive citizens within a free and democratic society. It is therefore that their training in critical thinking will allow them to contribute to the development of their countries. For this, mechanisms, suitable and possible didactic strategies must be sought to meet this challenge and therefore the Argumental Mind fact is presented, as a possible way to fulfill this educational task. The objective of the present study was to establish the Argumental Mind fact as a didactic strategy for teaching critical thinking in political science students. Looking for contributions to the pedagogical process to the problem posed, an investigation was carried out under the paradigm of qualitative character and Descriptive Dialectical Hermeneutical method, with a documentary design and aimed at the student population of Political Science of the University of Zulia. From the documentary review, the procedural findings were obtained that must be fulfilled to make use of the argumentative mind as a graphical way of discovering mechanisms for dismantling thesis, concepts in a diagrammatic way, which allow visualizing the mechanisms to make correct and pertinent interpretations of the different theoretical positions .